THE EFFECT OF STATION ROTATION MODEL ON STUDENTS’ ENGLISH PRONUNCIATION - Safira, Ega; Nappu, Syamsiarna; St. Asmayanti AM (FKIP Unismuh Makassar, 2023)
The objective of this study were to investigate (1) how is the effect of station rotation model on students’ Stress in pronouncing words at the eight grade of SMP Muhammadiyah Limbung and (2) how is the effect of station rotation model on students’ Intonation at the eight grade of SMP Muhammadiyah Limbung. The writer used pre-experimental research design with one group pre-test and post-test. The sample of this research was 20 students which was taken by purposive sampling technique. The data was analyzed using SPSS 28.00. The findings of the research proved that implementation of Station Rotation Model has a good effect on students’ English pronunciation in term stress and intonation. It could be seen from the students mean score between stress and intonation before and after using Station Rotation Model was pre-test on stress was 37.50 and post-test 64.50. While the students’ mean score of intonation was pre-tes 10.00 and post-test was 54.00. From the result of data analysis, it was indicated that the-test value of stress (9.423) was higher than t-table (1.729). While the t-test of intonation (6.242) was higher than t-table (1.729). Therefore, the study rejected the null hypothesis (H0) and accepted the alternative hypothesis (H1). After analyzing the data, it proved that the station rotation model has a good effect on students’ English pronunciation.